Study of Survivin: A Biomarker in Carcinoma Colon – An Original Study - Chandra, Pratibha; Kinra, Prateek (Annals of Pathology and Laboratory Medicine, 2020)
Background: Survivin, an anti-apoptotic protein has been of importance in colon carcinoma patient. Here we studied the prevalence of Survivin biomarker among cases of colon carcinoma and its relationship with other prognostic indicators. Design: Tissue samples from 102 patients with colon carcinoma were studied. H&E stain and immunohistochemistry were performed and evaluated. Immuno-histochemistry expression was sought according to IRS Scoring System (Immunoreactivity Scoring) for stain intensity and percentage positive cells. Survivin expression was also correlated with age at diagnosis, gender, grade, nodal status, lympho-vascular and perineural invasion, resection margins, Tumor stage (TNM) and Group Stage. Result and discussion: Survivin was expressed in high grade and stage tumors and showed significant association (p value= 0.002). Survivin expression was positive in lymph node positive tumors and showed significant association (p value= 0.002). Survivin was expressed in tumors with lympho-vascular and perineural invasion and showed significant association (p value= 0.02 and 0.001) respectively. Age at diagnosis showed significance of p=0.03 whereas Gender (Male/Female) and resection margins did not show any association with Survivin expression. Conclusion: Survivin expression increases as the tumor grade worsens in colon cancer and is maintained in approximately all high group staged tumors (TNM Staging) along with tumors showing lymphovascular and perineural invasion. Gender does not have any association.